2022
DOI: 10.28991/hij-2022-03-04-03
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Hybrid Learning in the University: A Case Study Approach

Abstract: Hybrid learning is a type of educational system in which some students attend class in person while others engage virtually from home. Hybrid learning has been applied in all educational institutions since the pandemic. BINUS University used a Learning Management System called Binusmaya to support teaching and learning activities for both hybrid and fully online learning. The objective of this study is to assess the effectiveness of hybrid learning at BINUS University based on student performance academically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 11 publications
0
1
0
Order By: Relevance
“…Similarly, these results provide evidence in favor of the fourth hypothesis, which generates a future challenge in the training of students [36][37][38]. The challenge is to contribute to the development of students' liking for statistics so that negative beliefs, fear, and avoidance behavior towards this subject decrease [39,40].…”
Section: -Discussionmentioning
confidence: 68%
“…Similarly, these results provide evidence in favor of the fourth hypothesis, which generates a future challenge in the training of students [36][37][38]. The challenge is to contribute to the development of students' liking for statistics so that negative beliefs, fear, and avoidance behavior towards this subject decrease [39,40].…”
Section: -Discussionmentioning
confidence: 68%
“…The results indicate that the arithmetic means of the responses of the study sample ranged between (3.92 -4.42), which are averages that fall within the high average and the very high average. 10,8,12,18,14,15,20,17,13,19,16) which came up. The results also indicated that the arithmetic mean at its highest level was for paragraph No.…”
Section: What Is the Level Of Development Of Creative Thinking In Emi...mentioning
confidence: 99%
“…The results indicate that the arithmetic averages of the responses of the study sample ranged between (4.09 -4.44), which are averages that fall within the high average and the very high average. (18,16,17,15,20,19) which came in high.…”
Section: What Is the Level Of Enabling The Safe Learning Environment ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Each model has its concept and characteristics that may affect the student's understanding and learning outcome [8]. Compared to fully online learning, blended learning is ineffective due to external factors like environment, knowledge, and skills [9]. To ensure that engineering students can stand a chance in competing in the industrial fields with the knowledge and skills required in management, planning, problem-solving and decisionmaking, blended learning models in the universities significantly impact the students.…”
Section: Introductionmentioning
confidence: 99%